IMPLEMENTASI BIMBINGAN MANASIK HAJI OLEH KANTOR KEMENTERIAN AGAMA DI KABUPATEN GORONTALO (The Implementation of Manasik Hajj Provided by The Office of Ministry of Religious Affairs in Gorontalo District) - M Taufik Hidayatulloh (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Ministry of Religious Affairs Republic Indonesia has responsibility in organizing and conducting hajj (pilgrimage). One of the important parts of the hajj execution is training of manasik hajj (guidance for those going on the hajj) which is conducted by ministry of religious affairs in a district and a municipality, including in Gorontalo district. This research aims to know the policy and the implementation of training of manasik hajj hold by office of ministry of religious affairs in Gorontalo district. This study uses a qualitative approach. Data were collected using interviews and documentary research. Data were analyzed using a technique offered by Miles and Huberman as follows; data reduction, data presentation, and drawing conclusion. Results of this study depict that the policy on hajj implemented by office of ministry of religious affairs in a district and sub district is followed the policy issued by the central office Ministry of Religious Affairs Republic of Indonesia in Jakarta. Furthermore, the implementation of such training in the district and sub-district level was in line with the central office with some adjustments.